Evaluation of Ferry Passenger Satisfaction in Batam City Based on Perceptions of Safety, Comfort, and Service Quality - Kelvin Saputra Mulyadi; Andri Irfan Rifai; Yusra Aulia Sari (Journal of Civil Engineering and Planning (JCEP), 2026)
Batam is a strategic gateway for international maritime transportation, connecting Indonesia with Singapore and Malaysia through ferry services. This study aims to evaluate ferry passenger satisfaction in Batam City based on three key service dimensions: safety, comfort, and service quality, and to examine their contribution to customer loyalty. A descriptive quantitative approach was employed using the Statistical Package for the Social Sciences (SPSS). Primary data were collected from 21 ferry passengers through a structured questionnaire using a five-point Likert scale. Descriptive statistical analysis was performed to identify response patterns and satisfaction levels. The results indicate that passengers are generally satisfied with the ferry services. The highest satisfaction scores were obtained for safety facilities, including life jackets and evacuation routes (4.38), crew friendliness (4.33), and seating and ventilation comfort (4.29). However, several aspects require improvement, particularly cabin tranquility (3.90), toilet cleanliness (3.95), and food and beverage services (4.00). Overall, ferry services in Batam have met passengers' basic expectations, although continuous improvements in supporting facilities and service quality are essential to enhance customer satisfaction and long-term passenger loyalty.